Performance study on a small-scale photovoltaic electrodialysis system for desalination. (July 2020) - Xu, Haiyang; Ji, Xu; Wang, Liuling; Huang, Jingxin; Han, Jingyang; Wang, Yue
Abstract: A small-scale photovoltaic (PV) direct drive electrodialysis system is proposed to explore the factors affecting the desalination performance. The electrodialysis desalination model is established, and is solved using MATLAB to investigate the influences of voltage, flow rate and electrolysis compartment size on performance factor β. This model is proved valid to predict the characteristics of photovoltaic electrodialysis system. The results show that the salinity at exit of the electrodialysis chamber decreases with the increase of the voltage and the ion membrane area, and increases with the increase of the flow rate. In typical sunny day, the salinity reaches below the standard value (<1000 ppm) by 20 minutes and 60 minutes earlier than in cloudy day and in overcast day, respectively. During the experiments, the cumulative freshwater is respectively 0.4L, 1L, 1.6L and 2.2L within 120 minutes at different flow rate. Highlights: Small-scale photovoltaic electrodialysis system was used for water desalination. The experimental results were compared with theoretical calculations. Theoretical calculations predict the experimental results well. Slower flow rate produces better water desalination and production of fresh water.